Ability Grouping: Is it better for mathematics classroom? - Kharel, Binita (Academic Journal of Mathematics Education, 2021)
This article concerns on ability grouping and mathematics classroom which is one of the most contentious issues in the present scenario. The purpose of the paper is to present argues on ability grouping in mathematics classroom in the context of Nepal. To address the mentioned purpose the author used the systematic literature review approach. Author presented different arguments and evidences based on different journal articles, books, essays dissertations and own teaching experiences. Presented arguments concluded that mathematics class without ability grouping instruction is positively impact on the academic performance of the students. It is hoped that the article assist to change the attitude of the concerned people toward ability grouping in mathematics classroom. The findings of this article would be useful implications for mathematics teacher students, as well as it opens the door to start a discourse on the ability grouping in mathematics classroom.